Island-size distributions of Ag on Pd(111) - Fauster, Thomas; et al. (Surface Review and Letters, 1996)
Island-size distributions of submonolayer Ag films on Pd(111) adsorbed at 90 K and after annealing of the film are recovered from two-photon photoemission spectra of the first image state. The inversion of the ill-conditioned problem with the maximum-entropy method reveals magic numbers in the island-size distributions. Hypothesis testing within the framework of Bayesian probability theory indicates a critical nucleus size i = 1. After annealing of the film large islands coexist with small clusters in a two-phase state.